Sign And Meaning Related To Hair Styles Found In Allure Magazine Cover - Darma Nopiyati (English Department, Faculty of Humanities, Andalas University, 2018)
The article focuses on the hairstyle related sign and meaning found on the cover of Allure Magazine. Data are collected from 8 magazine covers issued from January 2012 to February 2013. The theory of Linguistics signs and Non-linguistics sign proposed by Ferdinand de Saussure together with the theory of order of signification by Roland Barthes are employed in analyzing the data. The analysis showed that the sentences related to hairstyle are used to persuade the female reader to pay more attention to their hair care, the appliances and hair care products used in order to have an appearance like the models on the cover.